Event4You - Mobile application for event awareness / Mohamad Adib Hanafi Abdul Rashid - Abdul Rashid, Mohamad Adib Hanafi (2019)
The development of Event Awareness Mobile Application (Event4You) is a solution to people who want to travel and do not aware or acknowledge about event in Malaysia. The purpose of organising an event will be pointless if no people know about it. With development of Event4You, it will create a new way to give more exposure about the event. The main features of Event4You is displaying lists of events according by state. Event4You also give people to experience the nearby places function. People can see the nearby facilities around them in list view also give user an option to see it in map view.